Risk Management as a Basis for Integrated Water Cycle Management in Kazakhstan - Meyer, Burghard; Lundy, Lian; Watt, John; Abdullaev, Iskandar; Capilla Roma, Jose E. (Journal of Environmental Geography, 2016)
Integrated Water Cycle Management (IWCM) aims to bring together a diversity of social, environmental, technological and economic aspects to implement sustainable water and land management systems. This paper investigates the challenges and opportunities facing Kazakhstan as it its efforts to move towards a more sustainable approach to managing its finite and highly stressed water resources. The use of a strategic-level risk governance framework to support a multi-disciplinary Kazakh-EU consortium in working collaboratively towards enhancing capacity and capability to address identified challenges is described. With a clear focus on addressing capacity building needs, a strong emphasis is placed on developing taught integrated water cycle management programmes through communication, stakeholder engagement and policy development including appropriate tools for managing the water issues including hydraulic models, GIS-based systems and scenario developments. Conclusions on the benefits of implementing an EU-style Water Framework Directive for Central Asia based on a risk management approach in Kazakhstan are formulated.